Unravelling the cooperative role of lattice strain on MnO2/TiO2 and MnO2/ZnO catalysts for the fast decomposition of hydrogen peroxide. (18th May 2021) - Santhanaraj, D.; Selvamani, A.; Rajakumar, K.; Joseph, N. Ricky; Giridhar, S.; Adinaveen, T.; Sophie, P. Leema; Ramkumar, V.
Abstract : The rate of decomposition of hydrogen peroxide was directly correlated with lattice strain, as derived from strain calculations. Abstract : The influence of lattice strain on metal and metal oxide catalysts has been widely investigated by DFT calculations. However, it is still hard to prove by experimental methods. In the present investigation, we have explained how the experimentally obtained strain values are reflected in the catalytic decomposition of hydrogen peroxide by using MnO2 decorated on TiO2 and ZnO catalysts. The lattice strain parameter values have been derived from X-ray diffraction patterns using the modified Williamson–Hall (W–H) method. Uniquely, we observed that compressive strain could significantly affect the TOF of the reaction, especially on the MnO2 /TiO2 catalyst. Furthermore, the equilibrium constant calculated from the Langmuir–Hinshelwood (L–H) kinetic model shows that the MnO2 /TiO2 catalyst has a stronger adsorption capacity than the MnO2 /ZnO material. These results directly reflect the strength of the oxophilic sites and the lattice strain of the materials. A quantitative relationship has been established between lattice strain and catalytic activity.